RELATIONSHIP OF FAMILY SUPPORT WITH STRESS OF HEMODIALYSIS PATIENTS IN JOMBANG’S HOSPITAL IN THE HEMODIALYSISROOM (Studies inJombang’s Hospita in the Hemodialisa Room) - Muflichatul Muniroh; . Darsini; Ucik Indrawati (Jurnal Keperawatan, 2014)
The hemodialysis patients complained of many problems associated with the chance to move, the burden ofthe cost, load limiting fluid intake, and even the services provided by health workers, causing thehemodialysis patients experiencing stress. The purpose of this study is to determine the relationship of familysupport with the stress of hemodialysis patients in Jombang hospitals.The study design was a corelational with cross sectional that describe the stress experienced by hemodialysispatients in Jombang hospitals 2014. Sampling method was used purposive sampling. Samples were taken inhemodialysis patients who experience stress during May - June 2014 goten 60 respondents. Independentvariable is the family support and dependent variabel is hemodialilysis stress patients. Data retrievaltechniques by giving a questionnaire sheets to the respondent. After that the data was processed by theediting, coding, tabulating, and data entry.The results showed that nearly half of respondents provided support with good criteria by 28 respondents(46.66%) and also known the stress experienced by hemodialysis patients with mild stress as many as 29respondents (48.33%). Based on the analysis results through Spearman Rank's test with SPSS 16, obtained pvalue of 0.012 <0.05.The conclusion of this research is for family support to hemodialysis patients almost half of them was in goodcriteria, while hemolialysis stress patients almost half of them was in mild stress criteria. H1 accepted orthere was a relationship of family support with the stress of hemodialysis patients in Jombang hospitals.Keywords: Family Support, Stress, CRF, Haemodialysis